Hubungan Coping Style dan Anticipatory Grief pada Orangtua Anak yang Didiagnosis Kanker - Geni, Putri Lenggo; Rahmania, Qisthi (Humaniora, 2013)
Everyone copes with stressful events in his/her life differently. Three strategies in dealing with stress include problem-focused coping, emotion-focused coping, and religious-focused coping. Death of loved ones has been considered one of the major sources of stress in individuals and poses threat to their well being and adjustment if one?s failed to cope with the grief. Interestingly, previous studies show that families and caregivers of terminally ill patients suffered bereavement prior to the actual death, a phenomenon labeled anticipatory grief. Article presents a study with the purpose to investigate the relationship between different coping styles and anticipatory grief in parents of children diagnosed with cancer. Fifty-five parents, ranging from 20 to 60-year-old, participated in this study. Results revealed that coping style, particularly emotion-focused coping, significantly predict anticipatory grief in parents of children diagnosed with cancer. However, both problem-focused coping and religious-focused coping did not predict parental anticipatory grief in this study.